Newsprint grade Refiner Mechanical Pulps from Kenaf Sticks - Sharma, Y. K.; Dhawan, Rita; Karira, B. G. (Indian Forester, 1985)
Laboratory experiments were carried out on the production of refiner mechanical pulps from kenaf sticks and chemical (Soda) pulp from kenaf base fibre. The blending of the pulps indicates that newsprint grade pulps could be produced from a furnish containing 80 per cent refiner mechanical pulps of kenaf sticks and 40 per cant chemical (Soda) pulp of kenaf best fibre. Our earier studies have indicatad that kenaf best fibre shows Poof bleaching response. Hence, in the experiments only unbleached pulp was used.